2022
DOI: 10.3390/agriculture12091407
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Markers Associated with Physiological and Biochemical Traits during Storage of ‘Nam Dok Mai Si Thong’ Mango Fruits

Abstract: Mango ‘Nam dok mai si thong’ is in high demand worldwide, displaying desirable attributes which include a particularly sweet flavour and visually appealing appearance. Physiological and biochemical changes that occur in the fruit post-harvest are key factors in determining fruit quality and, consequently, predicted shelf life. In order to understand which post-harvest markers play crucial roles during the ripening process, as well as those which are a consequence of disease infection and physical damage caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Rapid off-tree ripening of mangoes are correlated with the loss of www.nature.com/scientificreports/ firmness and excessive softening during storage period, which ultimately reduces the required level of marketing of this precious fruit 10 . Natural ripening process positively affects the physiological and biochemical alteration in the mangoes, which includes, color changes, dehydration, cellular respiration, transformation of organic acids and polysaccharides, resultantly contributing towards good scores for organoleptic features of the mangoes 39 . Findings of Zhang et al 8 also revealed that firmness of the artificially ripened fruits got decreased with increasing the concentration of the ripening agents and with the passage of time, during storage period.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid off-tree ripening of mangoes are correlated with the loss of www.nature.com/scientificreports/ firmness and excessive softening during storage period, which ultimately reduces the required level of marketing of this precious fruit 10 . Natural ripening process positively affects the physiological and biochemical alteration in the mangoes, which includes, color changes, dehydration, cellular respiration, transformation of organic acids and polysaccharides, resultantly contributing towards good scores for organoleptic features of the mangoes 39 . Findings of Zhang et al 8 also revealed that firmness of the artificially ripened fruits got decreased with increasing the concentration of the ripening agents and with the passage of time, during storage period.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of longer ozone treatment times, these results also significantly differed from the control sample. As indicated by [23], many factors affect the content of total soluble solids (TSS) in stored plant raw materials. Conditions that positively influence the storage process significantly contribute to inhibiting the generation of this factor (TSS) in fresh commodities.…”
Section: Discussionmentioning
confidence: 99%
“…During the transition from maturity to edibility in the ripening process, physiochemical reactions increase the amount of simple sugars in the fruit. In addition, change in the fruit cell walls structure during ripening causes the flesh softening of the fruit (Tangpao et al, 2022 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%